O discurso de proprietários de academias sobre a prática da natação como atividade de lazer: inclusão ou elitização social? - Fabiano Pries Devide (Universidade Federal do Rio Grande do Sul, 2000)
The objectives of this study were: ¡) verify what the teachers who work with beginning swimming classes think about and how they manage the access of apprentices; and ii) discuss the function of the teachers who have their own swimming schools about the social inclusion of the community in the learning-how-to-swim process. Interviews with five teachers, owners of swimming schools have allowed us to conclude that: a) they have their customers from high middle class,- b) they have never offered to or had experiences with offering swimming classes to the community,- c) they consider their task as elitist,-d) they point out the lack of public pools for community work,- and e) they justify the absence of classes to the community based on the lack of association with other institutions,- on the prejudice of regular pupils,- and on the lack of community education. In short, we interpret that there is some fragility in these arguments, and lack of compromise from the owners about the acessibility in the learning-how-to-swim process as a leisure activity.